Wahiduddin Khan's Views on Modern Natural Science - Saidil Yusron (Penerbit Hellow Pustaka, 2025)
The study of nature and the natural processes that occur in the universe, including physics, chemistry, geology, astronomy, biology, and others. Natural science is considered one of the oldest sciences, seeking to understand the secrets of the universe and explain how it works and its composition. Natural science plays a vital role in understanding our world and explaining its phenomena and processes. Through this science, we can explore the phenomena around us and interact with the universe more broadly. It provides the scientific basis for technologies and innovations that impact and improve human life. Furthermore, natural science also contributes to improving health, the environment, sustainability, and economic development. Given this important role, does Islam have a place amidst these advances? In this article, the researcher aims to present arguments about the truth of Islam in the context of scientific evidence standards in modern studies, focusing on Wahiduddin Khan, who was interested in natural science and had a particular view of natural scientists. This article aims to reveal Wahiduddin Khan's position on natural scientists and his methods in critiquing their views.